(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Social transformation in Rajasthan after independence has been so tremendous that even one could doubt whether feudalism at all existed there or not. There is a remarkable discontinuity and departure in the post-independent Rajasthan from its feudal past. Nothing like a remarkable continuity persists for a nearly thousand years of society and polity, ecology and socio-cultural values of Rajasthan as perceived by Iqbal Narain P.C. Mathur Princes have own and lost elections. The Jagirdars and thikanedars have not only lost their status and power they have also degenerated into a pauperized lot. On the contrary the peasant castes have not only moved up socially economically they have become electorally a force to response with in India’s Parliament, State Legislatures and Panchayati Raj Institutions Certainly there is a vibrant new complexion of society and polity in the post-independence period.